A cross-sectional assessment of anemia and associated risk variables among different age groups in Gilgit-Baltistan - Younus, Waqar; Ali, Sartaj; Abbas, Ghulam; Hussasin, Azhar; Ali, Shamsher (International Journal of Pathology, 2024)
Background: Anemia poses a significant global health challenge and has a significant influence regarding both morbidity and mortality across diverse demographics. This cross-sectional study aim to assess the prevalence and risk variables associated with anemia in different age groups within the culturally diverse population of Gilgit-Baltistan (GB). Methods: The prevalence of anemia within each age group was determined through hemoglobin (Hb) level assessment using Hemocue Hb 201+ (HemoCue AB, Ängelholm, Sweden). This analysis encompassed various gender categories and examined the risk variables which contributing to anemia in GB. Samples were collected from different regions in order to obtain a representative sample of the population. A total of 720 individuals (386 males and 334 females) participated in this study. Results: About 32.40% males (65.2% mild, 31.7% moderate and 3.1% severe) and 56.07% females (36.5% mild, 46.3% moderate and 17.2% severe) were found anemic. Prevalence of anemia in male were highest in the age group 20-40 years (31.2%), followed by age group 10-19 years (26.4%) as compared to age group 41-60 (19.2%) and above 61 years (23.2%) and there mean hemoglobin level (Hb) was 11.98 ± 0.90 g/dL. Among females the highest prevalence were found in reproductive age 20-40 years (37.3%) and age between 10-19 (29.4%), followed by the age group 41-60 (13.4%) and above 61 years (19.7%) and mean hemoglobin level (Hb) was 9.93 ± 0.83 g/dL. Risk variables include socio economic status of respondents, the higher prevalence was found in lower class of the population (37.7% males and 43.6% Females). Conclusion: The findings highlight the vulnerability of both genders to anemia in GB. Addressing this public health concern requires research extending beyond the prevalence and socio-demographic factors. Future efforts should focus on developing iron-enriched formulas from locally accessible staple foods in GB to effectively combat this alarming condition.